Untangling lineage introductions, persistence and transmission drivers of HP-PRRSV sublineage 8.7 - Sun, Yankuo; Xing, Jiabao; Hong, Samuel L.; Bollen, Nena; Xu, Sijia; Li, Yue; Zhong, Jianhao; Gao, Xiaopeng; Zhu, Dihua; Liu, Jing; Gong, Lang; Zhou, Lei; et al. (Nature communications, 2024)
Despite a rapid expansion of Porcine reproductive and respiratory syndrome virus (PRRSV) sublineage 8.7 over recent years, very little is known about the patterns of virus evolution, dispersal, and the factors influencing this dispersal. Relying on a national PRRSV surveillance project established over 20 years ago, we expand the available genomic data of sublineage 8.7 from China. We perform independent interlineage and intralineage recombination analyses for the entire study period, which showed a heterogeneous recombination pattern. A series of Bayesian phylogeographic analyses uncover the role of Guangdong as an important infection hub within Asia. The spatial spread of PRRSV is highly linked with a composite of human activities and the heterogeneous provincial distribution of the swine industry, largely propelled by the smaller-scale Chinese rural farming systems in the past years. We sequence all four available modified live vaccines (MLVs) and perform genomic analyses with publicly available data, of which our results suggest a key “leaky” period spanning 2011–2017 with two concurrent amino acid mutations in ORF1a 957 and ORF2 250. Overall, our study provides an in-depth overview of the evolution, transmission dynamics, and potential leaky status of HP-PRRS MLVs, providing critical insights into new MLV development. There is limited epidemiological data on PRRSV sublineage 8.7 in Asia. Using national PRRSV surveillance data, the authors compiled a genomic dataset showing a geographically centralized spread, the likely impact of human-related activities on PRRSV spread and regional variability in interlineage recombination likelihood.